Variability, scalability and stability of microgrids - Muyeen, S. M.; Islam, Syed Mofizul; Blaabjerg, Frede (IET energy engineering series ;, 2019)
The book consists of 13 chapters and addresses three different mainstream technical challenges of microgrid - variability, scalability, and stability. With the term 'variability', the voltage and frequency fluctuations inside and outside microgrid boundaries are referred. On the other hand, 'stability' term includes voltage and frequency instabilities but also covers low voltage or zero voltage ride through problems. The 'scalability' part, in general, covers the optimization aspects of microgrid. The present development status and future trends of microgrid covering from generation, transmission, and distribution are presented based on the contributions from well-known researchers and academics from various disciplines.